2020
DOI: 10.1002/uog.21931
|View full text |Cite
|
Sign up to set email alerts
|

Absent ‘superimposed‐line’ sign: novel marker in early diagnosis of cleft of fetal secondary palate

Abstract: What are the novel findings of this work? We describe a new sonographic sign, the 'superimposedline' sign, for evaluation of the fetal secondary palate in early gestation on two-dimensional imaging of the vomeromaxillary junction in the midsagittal view. What are the clinical implications of this work? Inclusion of this sign during the routine nuchal translucency scan should improve screening and early detection of secondary palatine clefts. This sign also facilitates evaluation of cleft extension into the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…We present here the figures with PMD from the series of Lakshmy et al 1 . (Figure 1), indicating its correct measurement, and illustrate PMD assessment using an axial view (Figure 2a), showing the natural course of congenital cleft lip and palate 3 .…”
Section: Figurementioning
confidence: 87%
See 1 more Smart Citation
“…We present here the figures with PMD from the series of Lakshmy et al 1 . (Figure 1), indicating its correct measurement, and illustrate PMD assessment using an axial view (Figure 2a), showing the natural course of congenital cleft lip and palate 3 .…”
Section: Figurementioning
confidence: 87%
“…PMD should be measured as the shortest hyperechogenic distance between the ossified upper posterior palatine process and the anterior ossified portion of the We present here the figures with PMD from the series of Lakshmy et al 1 (Figure 1), indicating its correct measurement, and illustrate PMD assessment using an axial view (Figure 2a), showing the natural course of congenital cleft lip and palate 3 .…”
mentioning
confidence: 90%
“…However, threedimensional US (3D-US) allows the visualisation of complex 3D shapes and hence can be used to visualise the fetal palate. 4,[7][8][9] Maarse et al confirmed that 3D-US demonstrated a higher detection rate of cleft palate than 2D-US. 10 3D-US images that can demonstrate real anatomical structures are reconstructed based on high-fidelity information.…”
Section: Visualisation Of the Fetal Uvula On Three-dimensional Ultras...mentioning
confidence: 97%
“…The mid-sagittal view of the palatal line and the coronal view of the RNT are most useful for the diagnosis of secondary CP. Lakshmy et al 4 described the absent 'superimposed-line' sign as a novel marker for the early diagnosis of secondary CP. In this study, the coronal view of the fetal lip was difficult to identify before 12 weeks of gestation.…”
mentioning
confidence: 99%